A supersaturated Cu-Ag nanoalloy joint with ultrahigh shear strength and ultrafine nanoprecipitates for power electronic packaging. (10th May 2023) - Zhang, Wenwu; Zhang, Penghao; Lu, Dashi; Pan, Hao; Liu, Xiangli; Xu, Chengyan; Wei, Jun; Li, Mingyu; Ji, Hongjun
Highlights: The copper-silver core-shell nanopaste can conduct bonding with high quality. The supersaturated Ag-Cu nanoalloy joint exhibits ultrahigh shear strength (152 MPa). The strengthening mechanism of solid solution and ultrafine nanograin was proposed. High proportions of low-angle grain boundaries (7.44%) without deformation are rare. Ultrafine Copper nanoprecipitates can subordinately improve shear strength. Abstract: Ag-Cu bimetallic nanoalloy, integrating the advantages of reducing migration and cost of nano-Ag and alleviating oxidation of nano-Cu, is a prospective bonding material for power electronic packaging. The Ag-coated Cu nanoparticles (Cu@Ag NPs) paste can execute bonding with high quality at 250 °C, and the achieved supersaturated Ag-Cu nanoalloy joint with ultrahigh shear strength (152 MPa) dramatically exceeds most nano-paste joints. The interstitial solid solutions with atomic-level metallurgical bonds at the interface dominantly promoted the shear strength. Besides, the numerous ultrafine nanograin, high proportion of low angle grain boundaries (7.44%) without deformation, and the Cu nanoprecipitates in the joint would improve subordinately. Furthermore, the high content (16.8%) of Σ3 twin boundaries would contribute to the electrical and thermal conductivity. Thus, the multiple strengthening mechanisms with the solid solution, the second precipitated phase, and ultrafine nanograin can dramatically enhance shear strength and electro-thermal conductivity of joints for high-temperature device packaging.